Chemical elements content in goat milk, whey, cheese and yogurt from an ecological and conventional farm in Slovakia - Simona Almášiová; Róbert Toman; Martina PŠENKOVÁ; Vladimír TANČIN; Šimon MIKLÁŠ; Ivona JANČO (Journal of Central European Agriculture, 2023)
Milk and dairy products are an important part of the human diet for numerous reasons. Goat milk is higher in the content of elements such as K and Ca. Nowadays, consumption of goat milk and goat dairy products increases because of better digestion and therapeutic value. However, goat milk can contain heavy metals and trace elements as well which can harm human health. The content of 22 elements in sixty-nine samples of goat milk, whey, three types of cheese, and yogurt from the ecological farm in region Orava and conventional farm in region Stredné Považie in Slovakia was measured in this study. The highest concentration of four elements Ca, K, Mg, and Na in samples of goat products was found. In our study, significant statistical differences (P < 0.05) were found only in levels of K, Ca, Li and Na when comparing milk samples from organic and conventional farm. Concentrations of K (1260.50 mg/kg), Li (0.02 mg/kg) and Na (293.46 mg/kg) were higher in samples from ecological farm, while concentration of Ca (1344.65 mg/kg) was higher in samples from conventional farm. Toxic elements were present in trace amounts or under the limit of detection. The consumption of goat milk and goat dairy products from monitored farms can be considered as safe and beneficial for human health regardless of the way of farming. According to the highest level of strontium in hard ripening cheese, frequent regular consumption should be considered for children as a preventive measure for development of bone health.